Peran Kepolisian Dalam Pengawasan dan Pengendalian Minuman Beralkohol - Muhamad Irfan Seloaji; Arista Candra Irawati (Universitas Ngudi Waluyo, 2024)
Nowadays, alcohol abuse is a growing problem in society. Recently, there has been a huge uproar in the habit or culture among the public, namely that drinking alcoholic beverages, alcoholic beverages or alcoholic beverages are considered as something that has a negative stigma in the public mind, being called alcoholic beverages does not mean that they are strong but rather the effects they have on the body. Alcoholic drinks or what can be called liquor are drinks that are very dangerous for the human body because someone who consumes excessive alcohol can be at risk of experiencing several health problems, such as damage to vital organs, loss of body fluids, and decreased brain function. Moreover, quite a few victims died after drinking alcoholic beverages, especially mixed alcohol. The position of the police as law enforcement officers is expected to be able to monitor and regulate the distribution of alcoholic drinks in the Semarang Regency area. The author in this study used descriptive qualitative research. In general, descriptive research, including legal research, aims to accurately describe identities and conditions in society. This indication emerged because of the lack of understanding of the residents themselves. The position of the police in supervising and controlling alcoholic beverages in the Semarang district area is less than optimal, as evidenced by the fact that there are still many problems that arise due to one of them being the lack of socialization of regional regulations regarding alcoholic beverages from both the police and Satpol PP. The police only focus on repressive actions (raids) even though they are not often carried out because the public is not very familiar with the applicable regulations. This matter has become a polemic among residents because the circulation of alcohol is still rampant in the Semarang Regency area. In fact, with the large number of cases involving alcoholic drinks in Semarang Regency, the perpetrators range from young people to the elderly. The impact is that there are many fights, brawls, rapes, this is the responsibility of the Regency government. Semarang together with the Semarang Police to overcome this. Abstrak Penyalahgunaan minuman keras dewasa ini adalah kasus yang lumayan bertumbuh di masyarakat. Akhir- akhir ini gempar sekali kebiasaan ataupun budaya di tengah publik ialah minum minuman beralkohol, minuman beralkohol ataupun minuman keras dianggap selaku suatu yang mempunyai stigma negatif ditengah pemikiran publik, dengan dinamakannya minuman keras bukan berarti bentuknya yang keras melainkan akibat yang ditimbulkannya terhadap badan. Minuman beralkohol ataupun yang dapat diucap miras merupakan minuman yang sangat beresiko untuk badan manusia sebab seorang yang komsumsi alkohol berlebih dapat berisiko hadapi beberapa permasalahan kesehatan, semacam rusaknya organ vital, kehilangan cairan tubuh, sampai menurunya kerja otak. Apalagi tidak sedikit korban wafat sehabis menenggak minuman keras, paling utama miras oplosan. Kedudukan kepolisian selaku aparat penegak hukum diharapkan sanggup mengawasi sekaligus mengatur peredaran minuman beralkohol di daerah Kabupaten Semarang. Penulis dalam penelitian ini memakai riset yang sifatnya deskriptif kualitatif. Pada biasanya riset deskriptif tercantum riset hukum bertujuan guna menggambarkan secara pas identitas, kondisi dalam masyarakat. Indikasi tersebut mencuat sebab minimnya pemahaman warga itu sendiri. Kedudukan kepolisian dalam pengawasan serta pengendalian minuman beralkohol di daerah kabupaten semarang kurang maksimal dibuktikan dengan masih banyak masalah- masalah terjalin disebabkan salah satunya minimnya sosialisasi peraturan wilayah tentang minuman keras baik dari pihak kepolisian serta satpol pp. Pihak kepolisian cuma berfokus dalam aksi represif( razia) meski tidak kerap dicoba sebaliknya masyarakat belum banyak mengenali ketentuan yang berlaku. Perihal ini jadi polemik di tengah warga sebab masih maraknya peredaran miras di daerah Kabupaten Semarang faktanya dengan banyaknya kasus- kasus tentang minuman beralkohol di Kabupaten Semarang pelakunya mulai dari anak muda sampai berusia dampaknya merupakan banyaknya perkelahian, tawuran, pemerkosaan ini jadi tanggung jawab untuk pemerintah Kabupaten Semarang bersama- sama Polres Semarang buat mengatasinya.